Quality of work life and risk of sexual dysfunction in nurses - Andrade-Tasayco, Andrea Verónica (2023)
Unsatisfactory personal experiences and relationships in the work environmentare associated with negative sexual outcomes. Female sexual dysfunction (FSD) isthe disturbance of any of the phases of orgasm. Quality of work life (QWL) is theworker's perception between work demands and coping techniques. Objective.: Todetermine the association between quality of work life and the risk of female sexualdysfunction in nurses of a public hospital in Callao, Peru. Methods: Observational,cross-sectional, analytical study conducted in nurses of the Hospital NacionalDaniel Alcides Carrión (HNDAC) of the Constitutional province of Callao, Peru. Therisk of FSD was measured with the Rosen test. CVL was measured with the CVP-35 questionnaire. Statistical analysis was performed with the STATA version 15program. A value of p<0.05 with a 95% CI was considered significant. Results: Thestudy involved 168 nurses who responded completely. The dimensions of CVLassociated with DSF were direct support (p=0.01), intrinsic motivation (p=0.003),the question on work disconnection (p=0.007), monthly income (p=0.003), maritalstatus (p=0.001) and alcohol consumption (p=0.014). There was no association inthe multivariate analysis. Conclusion: In the present study there was no associationbetween dimensions of quality of work life and confounder-adjusted risk of femalesexual dysfunction.